Exploring the Role of Psycho-Social Factors on the Recidivism of Homicide Offenders - Reid, Jonathan C.; Oliveira, Raquel V. [UNESP]; Collier, Nicole (SAGE Publications, 2023)
Research on criminal recidivism is extensive. However, little is known about how cumulative risk factors influence recidivism, specifically among homicide offenders. The current study examines the effect of cumulative psychological and social risk factors on recidivism patterns for homicide offenders released in Florida between 2004 and 2011. Analyses of 4,323 homicide offenders indicate that the influence of cumulative psycho-social risk factors varies depending on the measure of recidivism and the statistical method used. The implications of these findings for theory and research are considered.
Keywords: cumulative effects; homicide offenders; life-course; mental health; re-offending; recidivism